GENETIC DIVERSITY OF OCTOPUS MINOR (S ASAKI, 1920) INFERRED BY MITOCHONDRIAL NADH DEHYDROGENASE SUBUNIT 2 GENE. - F. Muhammad; L. Liu; Z.M. Lü; L. Gong; X. Du; M. Shafi; B. Waryani; H.A. Kaleri (Journal of Animal and Plant Sciences, 2018)
Octopus minor is an economically important resource commonly found in Chinese coastal waters. Mitochondrial DNA NADH dehydrogenase subunit 2 ( ND2) gene were applied to assess genetic variation among eight populations collected from northern to southern part of China coast. Twenty four haplotypes were detected from 112 individuals of eight populations. Overall high haplotype (0.813) and low nucleotide diversity (0.044) was observed. AMOVA revealed (88.78%) variation among population and ( 11.22%) within population. The pairwise F ranged between ( -0.011 to ST 0.992. Gene flow (N ) of Wenzhou and Dongshan population was much lower among others. Neighbour joining (NJ) m tree clustered eight populations into three clades. Network analysis revealed that two (Hap1- Hap 9) haplotypes appeared in six and four populations respectively. The mismatch distribution showed unimodal pattern in calde two and three which suggested population expansion while clade one showed stability. The deviation might be result of several causes including low dissemination ability, influenced by late Pleistocene geological period or Changiang River outflow on population structure of O.minor. These results will enhance our understanding for better exploitation, protection and management of O.minor. using mitochondrial DNA genes which have high
Keywords: Cephalopod; Octopus minor; ND 2; Genetic diversity; Chinese waters.